Antisense-derived HIV-1 cryptic epitopes are not major drivers of viral evolution during the acute phase of infection - Peng, Binghao J; Carlson, Jonathan M.; Liu, Michael KP; Gao, Feng; Goonetilleke, Nilu; McMichael, Andrew J; Borrow, Persephone; Gilmour, Jill; Heath, Sonya L; Hunter, Eric; Bansal, Anju; Goepfert, Paul A (Journal of Virology, 2018)
ABSTRACT While prior studies have demonstrated that CD8 T cell responses to cryptic epitopes (CE) are readily detectable during HIV-1 infection, their ability to drive escape mutations following acute infection is unknown. We predicted 66 CE in a Zambian acute infection cohort based on escape mutations occurring within or near the putatively predicted HLA-I-restricted epitopes. The CE were evaluated for CD8 T cell responses for patients with chronic and acute HIV infections. Of the 66 predicted CE, 10 were recognized in 8/32 and 4/11 patients with chronic and acute infections, respectively. The immunogenic CE were all derived from a single antisense reading frame within pol. However, when these CE were tested using longitudinal study samples, CE-specific T cell responses were detected but did not consistently select for viral escape mutations. Thus, while we demonstrated that CE are immunogenic in acute infection, the immune responses to CE are not major drivers of viral escape in the initial stages of HIV infection. The latter finding may be due to either the subdominant nature of CE-specific responses, the low antigen sensitivity, or the magnitude of CE responses during acute infections. IMPORTANCE Although prior studies demonstrated that cryptic epitopes of HIV-1 induce CD8 T cell responses, evidence that targeting these epitopes drives HIV escape mutations has been substantially limited, and no studies have addressed this question following acute infection. In this comprehensive study, we utilized longitudinal viral sequencing data obtained from three separate acute infection cohorts to predict potential cryptic epitopes based on HLA-I-associated viral escape. Our data show that cryptic epitopes are immunogenic during acute infection and that many of the responses they elicit are toward translation products of HIV-1 antisense reading frames. However, despite cryptic epitope targeting, our study did not find any evidence of early CD8-mediated immune escape. Nevertheless, improving cryptic epitope-specific CD8 T cell responses may still be beneficial in both preventative and therapeutic HIV-1 vaccines.